Penerapan Pembelajaran Tematik Terpadu di Sekolah Dasar - Novika Auliyana Sari; Sa’dun Akbar; Yuniastuti Yuniastuti (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This research was aimed to describe the planning, implementation, assessment, obstacles, efforts, and impacts in the application of integrated thematic learning in SDN Purwoasri 2 and SDN Mranggen in Kediri. This research is a qualitative descriptive. The data of this study were collected through observation, interview and document study. The results showed (1) lesson planning, teachers successfully designed lesson plans covering all components of curriculum 2013, (2) implementation, the teacher used thematic by integrating subjects on basic competencies and learning activities using a scientific approach, (3) assessment, including knowledge, attitudes and skills, (4) obstacles, the limited time in designing lesson plans, lack of teaching variation, difficulties in stimulating questioning activities, limited facilities and assessment, (5) efforts, the teacher prepares lesson plans, variations in learning, uses the media and the surrounding environment, follows the KKG on assessment, (6) the impact of knowledge is lower than students' skills and attitudes.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan perencanaan, pelaksanaan, penilaian, hambatan, upaya, dan dampak pembelajaran tematik terpadu di SDN Purwoasri 2 dan SDN Mranggen. Penelitian menggunakan deskriptif kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara, dan studi dokumen. Hasil penelitian (1) perencanaan, guru membuat RPP sesuai komponen Kurikulum 2013, (2) pelaksanaan, guru memadukan KD pada mata pelajaran (tematik) melalui pendekatan saintifik, (3) penilaian, mencakup pengetahuan, sikap, dan keterampilan, (4) hambatan, alokasi waktu membuat RPP, variasi belajar, kegiatan menanya, sarana prasarana dan penilaian masih kurang, (5) upaya, guru menyusun RPP, variasi belajar, menggunakan media dan lingkungan sekitar, mengikuti KKG tentang penilaian, (6) dampak pengetahuan lebih rendah dibandingkan keterampilan dan sikap siswa.